Considering application domain ontologies for data mining - mota pinto, filipe (2009)
The dramatically explosion of data and the growing number of different data sources are exposing researchers to a new challenge - how to acquire, maintain and share knowledge from large databases in the context of rapidly applied and evolving research. This paper describes a research of an ontological approach for leveraging the semantic content of ontologies to improve knowledge discovery in databases. We analyze how ontologies and knowledge discovery process may interoperate and present our efforts to bridge the two fields, knowledge discovery in databases and ontology learning for successful database usage projects.